Modelling public health improvements as a result of air pollution control policies in the UK over four decades—1970 to 2010 - Carnell, EJ; Vieno, M; Vardoulakis, S; Beck, RC; Heaviside, C; Tomlinson, S; Dragosits, U; Heal, MR; Reis, S (IOP Science, 2019)
In much of the industrialised world, policy interventions to address the challenges of wide-spread air pollution as resulting from development and economic progress in the 2nd half of the 20th century have overall led to reductions in air pollution levels and related health effects since the 1970s. While overall improvements towards reducing health effects from ambient air pollution are recorded, comprehensive and consistent assessments of the long-term impact of policy interventions are still scarce. In this paper, we conduct a model assessment over a 40 year period of air pollution in the UK. In order to correct for the short and longer term variability of meteorological factors contributing to trends in ambient concentrations of priority air pollutants (nitrogen dioxide, sulphur dioxide, fine particulate matter and ozone), we use a fixed meteorological year for all model simulations. Hence, the modelled changes in air pollutant concentrations and related health effects are solely a function of the changes in emissions since 1970. These changes in emissions are primarily driven by policy interventions, ranging from phasing out of specific fuels or substances, to regulating the use of chemicals and driving the development of cleaner, more efficient technologies. Over the 40 year period, UK attributable mortality due to exposure to PM2.5 and NO2 have declined by 56% and 44% respectively, while ozone attributable respiratory mortality increased by 17% over the same period (however, with a slight decrease by 14% between 2000 and 2010).